Information and analytic evaluation of activity indicators of medical staff in the dental clinic - Mulesa, Oksana; Snytyuk, Vitaliy; Trombola, Mykhailo; Ivazkevych, Viktoriia (Technology audit and production reserves, 2020)
Evaluation of the activities of an economic entity in any sphere of the national economy is an important process at all stages of the existence of such an entity. The results of this evaluation affect the planning of the institution for future periods of time, the formation of its personnel policy, the reorganization and the like. At the same time, facilities of the service sector should be considered separately, in addition to indicators reflecting the profit of the institution, indicators characterizing the quality of the services provided by the institution are also important. The object of the research is the processes of informational and analytical support for making managerial decisions to evaluate the effectiveness of the staff of dental clinics. Such support is necessary to analyze operational information about the activities of medical workers and make timely and effective decisions to optimize their activities in order to improve the quality of medical services. Particular attention should be paid to determining the criteria for the effectiveness of medical personnel. In the work, methods of system analysis were used to study the processes of the activities of dental clinic workers when they provided medical services. As well as methods of mathematical modeling – to formalize the tasks that arise in the process of evaluating the performance of medical workers and a systematic approach – when analyzing the problem of information and analytical support in the process of evaluating the performance of medical workers. In the course of the study, a method is proposed to increase the efficiency of managerial decision-making processes for the activities of dental clinics based on an analysis of the performance indicators of their employees by developing and implementing relevant software. An information-analytical system has been developed that allows to calculate and visualize in a convenient form the ratio between such indicators of medical workers as normative and actual load. The use of the developed software product will allow to develop and make timely and informed management decisions on the activities of dental clinics.